Inner gnawing, outward clawing - The role of existential crises in crime causation. (January 2019) - Bennett, John T.
Abstract: This paper provides an interdisciplinary perspective on the role of existential crises in crime causation. The theory presented in this paper is that a crisis of meaning is interrelated with other criminogenic factors, and that these factors together lead to frustration, which in turn may lead to aggression in some cases. Specifically, factors of anomie, boredom, mass entertainment, subculture, and gender are explored. This framework traces the influence of both social structure and culture on the individual level of motivation. This paper follows in the theoretical tradition advanced by Dollard et al., linking frustration to aggression and positing "there is a strong tendency for inhibited direct aggression to be displaced, i.e., not to disappear but to be expressed in altered form or to be directed toward individuals who were not the source of the frustration." (Dollard, 1967). The paper develops a Weberian ideal type of the anomic individual within the criminal subculture. For an additional layer of social psychological perspective, the analysis continually engages with Merton's theory of anomie. Overall, this framework invites the reader to explore the interaction of psychological, sociological, and cultural variables. By appreciating the relationship between these variables, we might recognize the motivational power of the subjective experience of acute frustration present during existential crises. The results of this analysis are directly applicable to the perennial social issue of aggression. Scholarly elucidation of the criminogenic existential crisis can provide vivid guidance to teachers, parole officers, social work professionals, and therapists from a variety of traditions. The existential perspective provides an important reason to remain attuned to the psychological vulnerability of young people. Primarily, the need for meaning-oriented leadership should be seriously considered. Another basic precept of prevention should be to provide young people with a third way between models of ostentatious affluence and nihilistic ego gratification. Additionally, boredom should be recognized as a criminogenic state of being. Importantly, the pervasiveness of criminal subcultures must be reckoned with. Rather than denying the pervasiveness of such subcultures, preventive policy should incorporate destructive or unflattering norms and behavior into a positive framework of counseling or therapy. Finally, supervision during the period of inner crisis is absolutely vital. Constructive supervision would consist of ensuring that external control is concurrent with purposeful activity and outlets for inevitable frustrations. This framework has implications for criminal justice. By focusing closely -as this paper does- on psychological drives, we begin to perceive limitations to punitive policy. As this paper suggests, external controls may merely redirect inner drives, which will tend to discover or create outlets once the external control is removed.